Improving Gender Wage Equality Reduces Intimate Partner Violence in Brazil : Policy Implications for Mothers - Reynolds, Sarah Anne (World Bank, Washington, DC, 2021)
More wage equality for women reduces violence against women in urban Brazil. Evidence shows that violence has declined at various levels of severity. Wage equality may be improved through family-friendly policies such as preschool provision and maternity leave. Public safety and legal protections are also needed.